Implementing the Storwize V7000 and the IBM System Storage SAN32B-E4 Encryption Switch - Tate, Jon (IBM redbooks., 2012)
In this IBM® Redbooks® publication, we describe how these products can be combined to provide an encryption and virtualization solution: IBM System Storage® SAN32B-E4 Encryption Switch IBM Storwize® V7000 IBM Tivoli® Key Lifecycle Manager This book is intended for anyone who needs to understand and implement the IBM System Storage SAN32B-E4 Encryption Switch, IBM Storwize V7000, IBM Tivoli Key Lifecycle Manager, and encryption.